Synthesis of asymmetrically meso -substituted porphyrins bearing amino groups as potential cationic photodynamic agents - Caminos, Daniel Alberto (2005)
Novel asymmetrically meso-substituted porphyrins bearing amino groups have been synthesized as precursors of cationic photodynamic agents. The amphiphilic character of these porphyrins was increased by the presence of a high lipophilic trifluoromethyl group. Different patterns of porphyrin structures were obtained from meso-4-[(3-N,N-dimethylaminopropoxy)phenyl] dipyrromethane 1, which was formed by the condensation of 4-(3-N,N-dimethylaminopropoxy) benzaldehyde with a large excess of pyrrole. This reaction takes place at high temperature with a yield of 59%. This reaction was also attempted under acid-catalyzed condensation at room temperature. However, under these conditions, the amino group reduces the catalyst and the reaction does not take place. To obtain porphyrins, dipyrromethane 1 was condensed with aldehydes in the presence of trifluoroacetic acid (TFA) under different conditions. First, 1 reacted with 4-(3-N,N-dimethylaminopropoxy)benzaldehyde in dichloromethane catalyzed by TFA (~4 times TFA/1 molar ratio) to obtain 6.2% of 5,10,15,20-tetrakis(4-[3-N,N-dimethylaminopropoxy]phenyl)porphyrin (A4-porphyrin). Under similar conditions, reaction of 1 with 4-(trifluoromethyl)benzaldehyde produces 5,15-di(4-[3-N,N-dimethylaminopropoxy]phenyl)-10,20- di(4-trifluoromethylphenyl)porphyrin (A2B2-porphyrin) with a 4.8% yield. This procedure also yields a mixture of porphyrins, which were formed due to acidolysis of 1. When a minor amount of TFA was used in acetonitrile, the yield of A2B2-porphyrin was very poor (~0.4%). On the other hand, condensation of 1 with 4-trifluoromethylbenzaldehyde and 4-(3-N,N-dimethylaminopropoxy)benzaldehyde catalyzed by TFA (~2 times TFA/1 molar ratio) in acetonitrile yields 9.3% of 5-(4-trifluoromethylphenyl)-10,15,20- tris(4-[3-N,N-dimethylaminopropoxy]phenyl)porphyrin (A3B-porphyrin). A2B2 and A4 porphyrins were also isolated with 6.0 and 2.0%, respectively. Finally, exhaustive methylation of amino porphyrins produces cationic sensitizers (>94% yield). Absorption and fluorescence spectroscopic studies of these sensitizers were compared in N,N-dimethylformamide. In these porphyrins, the cationic centers are isolated from the porphyrin ring by a propoxy bridge. Thus, the cationic charges have minimal influence on the photophysical properties of the sensitizers. In addition, this chain provides a higher mobility of the charge, which could facilitate interaction with the outer membrane of the Gram-negative bacteria. These amphiphilic cationic porphyrins are promising photosensitizers with potential applications in bacterial inactivation by photodynamic therapy.